The Impact of the Internal Audit Function on the Determinants of the Usefulness of Accounting Information A Field Study of the Opinions of Internal Auditors Preparing Financial Statements in Libyan Commercial Banks (Al-Farooq Journal of Sciences, 2026)
This study aimed primarily to measure and evaluate the impact of the internal audit function (both assurance and advisory) on the determinants of the usefulness of accounting information in Libyan commercial banks in the western region. It focused on two fundamental quality attributes: the credibility of information (truthful representation) with its dimensions of (truthfulness, objectivity, verifiability, and comparability), and the relevance of information with its dimensions of (timeliness, predictive power, and confirmatory power). The study also sought to determine whether there were statistically significant differences in the attitudes of the target groups.To achieve its objectives, the study employed a descriptive-analytical approach. A questionnaire was used as the primary tool for collecting field data from the study population, which consisted of two main groups: internal auditors and financial statement preparers (accountants) in commercial banks. The collected data were analyzed using a range of appropriate statistical methods, including descriptive and inferential statistics. Statistical tests such as the One Samples t-test and the Independent Samples t-test were employed.The study results showed a statistically significant impact of the internal audit function on the determinants of the usefulness of accounting information (truthful representation and relevance) in Libyan commercial banks in the western region. Furthermore, there was a general consensus between internal auditors and financial statement preparers regarding the prominent positive role of the internal audit function in ensuring the quality of accounting practices, confirming truthful representation, and enhancing the relevance of accounting information.Based on these findings, the researchers recommend providing greater organizational and financial support to internal audit functions in commercial banks, strengthening their operational and organizational independence to guarantee the impartiality and objectivity of financial reporting, activating the advisory aspects of internal audit alongside its traditional confirmatory role, and utilizing continuous evaluation reports to improve the timeliness and predictive value of accounting data.
Keywords: Function – Audit – Internal – Determinants – Benefit – Information – Accounting